Etika Muamalah dalam Perspektif Al-Qur’an: Tafsir Keadilan dan Kejujuran pada QS. Al-An'am 152 dan QS. Hud 85 - Anne Agnia Nurhasanah; Indi Aulia Fajri; Merry Siti Mariam; Mualim (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
This research is motivated by the continued prevalence of muamalah practices that deviate from the values ​​of justice and honesty, such as fraudulent transactions and abuse of the rights of the weak, so that it is necessary to strengthen muamalah ethics based on the Qur'an. The purpose of this study is to analyze the concept of muamalah ethics from the perspective of the Qur'an through the interpretation of QS. Al-An'am verse 152 and QS. Hud verse 85, with a focus on the values ​​of justice, honesty, and trustworthiness in socio-economic life. This study uses a qualitative method with a thematic interpretation approach (maudhu'i), through a literature review of the Qur'an, classical and contemporary interpretations, hadith, and other supporting sources. The results of this study indicate that justice (‘adl and al-qisṭ) in muamalah is not only normative but also applicable, encompassing the obligation to perfect measures and weights, maintain transaction transparency, and protect the rights of vulnerable parties such as orphans. The research findings reveal that QS. Hud 85 emphasizes the social impact of economic fraud, while QS. Al-An‘am 152 emphasizes the dimensions of trust and moral responsibility in wealth management. The implications of this study confirm that internalizing the values ​​of justice and honesty in muamalah plays a crucial role in creating socio-economic stability, strengthening public trust, and building a just, moral, and sustainable Islamic economic system.